ANALISIS PENGARUH PERKEMBANGAN DANA PERBANKAN, DANA PIHAK KETIGA PERBANKAN SYARIAH, DAN POSISI KREDIT PERBANKAN TERHADAP POSISI KREDIT USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI INDONESIA YANG TERDAFTAR STATISTIK EKONOMI KEUANGAN INDONESIA - Fitriani, Nur; Budi Marwoto, Pan; Prima Nugroho, Stefanus (Jurnal Akuntansi Bisnis Dan Keuangan, 2018)
The research's main purpose of this study is to prove and verify the effect of Banking Funds, Third Party Funds of Sharia Banking, and Bank Loan Positions on Micro, Small, and Medium Business Credit positions in Indonesia. The technique of processing and data analysis in this research uses Multiple Linear Regression Analysis and hypothesis testing. Hypothesis testing using t-test and F-test with 5% significance level. This study also uses the Coefficient of Determination (R2) to determine the ability of independent variables in explaining the dependent variable. The result of the simultaneous hypothesis test (F-test) shows that the Development of Banking Funds, Third Party Funds of Sharia Banking, and Banking Credit Position simultaneously affect the Position of Micro, Small, and Medium Business Credit in Indonesia. The result of the partial hypothesis test shows that Third Party Funds of Syariah Banking have a positive effect on the Credit Position of Micro, Small, and Medium Enterprises in Indonesia. Value of Coefficient of Determination (R2) of 0.904 This value can be defined that 90.4% of Micro, Small, and Medium Business Loan Position In Indonesia can be explained by the Development of Banking Funds, Third Party Funds of Sharia Banking and Position of Banking Credit. While the remaining 9.6% is explained by other factors outside this study.